2013
DOI: 10.1111/1754-9485.12089
|View full text |Cite
|
Sign up to set email alerts
|

Prostate bed motion may cause geographic miss in post‐prostatectomy image‐guided intensity‐modulated radiotherapy

Abstract: Variability was seen in all planes for the movement of both surgical clips. The greatest movement occurred in the anterior-posterior plane in the upper prostate bed, which could cause geographic miss of treatment delivery. The variability in the movement of the superior and inferior clips indicates a prostate bed tilt that would be difficult to correct with standard online matching techniques. This creates a strong argument for using anisotropic planning target volume margins in post-prostatectomy radiotherapy. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 20 publications
2
43
1
Order By: Relevance
“…The DRT exceeded the predetermined 3‐mm threshold for the 95% LoA by 1.12 mm in this direction. This variance is not unexpected given the largest motion of the prostate bed and remnant seminal vesicles is known to occur in the AP direction and that prostate bed position can often be independent of the seminal vesicles . The DRT uses an algorithm to match to grey values within the pre‐determined mask and, when deformation occurs a best fit of these soft tissues is calculated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DRT exceeded the predetermined 3‐mm threshold for the 95% LoA by 1.12 mm in this direction. This variance is not unexpected given the largest motion of the prostate bed and remnant seminal vesicles is known to occur in the AP direction and that prostate bed position can often be independent of the seminal vesicles . The DRT uses an algorithm to match to grey values within the pre‐determined mask and, when deformation occurs a best fit of these soft tissues is calculated.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in imaging systems such as in‐room cone beam computerised tomography (CBCT) have improved image‐guided radiation therapy, allowing tumour volumes to be more accurately localised prior to treatment . This is particularly important for patients receiving radiotherapy for prostate cancer following prostatectomy surgery as the prostate bed moves independently of bones within the pelvis . Many authors have studied the motion of the prostate bed and found that involuntary filling of the rectum and bladder can cause a geographical miss of the tumour volume or inclusion of organs at risk in the high dose region of the treatment volume .…”
Section: Introductionmentioning
confidence: 99%
“…Previous authors have reported that the PB moves independently of bony anatomy, [15][16][17][18][19] and in a number of these studies CBCT scans were used to assess this movement. 10,20,21 This has implications for daily image guidance techniques applied during radiotherapy treatment in post-prostatectomy patients. The use of the IMRT treatment technique makes treatment accuracy even more important, due to the highly conformal dose distributions achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Standard practice for image verification during post‐prostatectomy radiotherapy (PPRT) is to align to bony anatomy on either kV or CBCT imaging. However, it has been found that the PB can move independently of the bony anatomy, therefore making bony anatomy a poor surrogate for PB position …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation